1973
DOI: 10.1002/jez.1401840311
|View full text |Cite
|
Sign up to set email alerts
|

Relations of prolactin and thyroid hormone to molting, skin texture, and cutaneous secretion in the red‐spotted newt

Abstract: The effects of prolactin on skin texture, on cutaneous secretion and on molting have been examined in the red-spotted newt under several hormonal conditions. In the adult newt skin is smooth and is covered with varying amounts of cutaneous secretion. Under laboratory conditions the skin ordinarily becomes rough and tuberculated within one or two weeks. Doses of 1.2-120 units of prolactin caused the skin of intact, laboratory-conditioned, red-spotted newts to become smooth and slimy. Similar changes were seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 26 publications
(1 reference statement)
2
10
0
Order By: Relevance
“…Prl can control skin molting in newts (Dent et al 1973) and feather molting in avian species (Dawson and Sharp 1998;Dawson et al 2009;Crossin et al 2012). Seasonal Prl in combination with other hormones is thought to modulate annual changes in hair growth of several species, including sheep, deer, and voles (Duncan and Goldman 1984;Curlewis et al 1988;Smale et al 1990;Dicks et al 1996;Nixon et al 2002;Randall 2007).…”
Section: Prl: a Conserved And Global Regulator Of Tissue Regenerationmentioning
confidence: 99%
“…Prl can control skin molting in newts (Dent et al 1973) and feather molting in avian species (Dawson and Sharp 1998;Dawson et al 2009;Crossin et al 2012). Seasonal Prl in combination with other hormones is thought to modulate annual changes in hair growth of several species, including sheep, deer, and voles (Duncan and Goldman 1984;Curlewis et al 1988;Smale et al 1990;Dicks et al 1996;Nixon et al 2002;Randall 2007).…”
Section: Prl: a Conserved And Global Regulator Of Tissue Regenerationmentioning
confidence: 99%
“…The second metamorphosis includes PRL-induced changes in which the rough skin of the eft becomes smooth and slimy. Similar changes can be induced in the adult (Dent et al, 1973;Dent, 1975). In adult newts, prolactin functions singly, or in combination with testosterone, to promote the development of male secondary sexual characteristics including increased tail fin height (Chadwick, 1940, 19411, formation of nuptial pads (Singhas and Dent, 1975) and stimulation of product synthesis and discharge from hedonic glands (Pool and Dent, 1977).…”
Section: Mentmentioning
confidence: 96%
“…that when newts of either sex are maintained in water at 4"C, skin texture and cutaneous secretory activity remain constant; however, when animals are maintained at 22-23"C7 the epidermis becomes rough and secretory activity diminishes within 2-3 weeks (Dent et al, 1973;Hoffman and Dent, 1978). Similarly, it has been observed that during the summer months the skin of freshly collected animals lacks the smooth and slimy texture that persists during the remainder of the year (Singhas, unpublished).…”
Section: Mentmentioning
confidence: 98%
“…In reptiles and amphibians, PRL promotes molting of the epidermis. 17 PRL stimulates skin melanocyte growth in fishes and mammals, 18,19 and keratinocyte growth in mammals. 20 In birds, PRL induces defeathering and epidermal growth of the incubation patch.…”
Section: Possible Primary Function Of Prolactin: Cell Proliferation/amentioning
confidence: 99%